Radar scanning the world production frontier - Jens J. Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2015)
In this paper we report the results from a detailed investigation of the shifts of the world production frontier function over the period 1980-2010. Analogous to a radar we implement a novel measurement approach for these shifts using nonparametrically computed productivity measures to scan the frontier shifts across the entire input-output space. The shifts of the frontier function measured in this way are analyzed by various regression methods (including robust and nonparametric). The results point towards substantial non-neutrality of technological progress and furthermore show that technological progress is more pronounced in regions of high output per worker and in regions where physical and human capital are intensely used.
Keywords: C14; E23; O11; O47; 330; non-neutral technological change; world production frontier; nonparametric frontier function